PATRONES DE LIDERAZGO EN GERENTES ECUATORIANOS: EL IMPACTO DE GÉNERO Y EDUCACIÓN - Solis, Eduardo; Elgoibar, Patricia (Revista Inclusiones, 2019)
The study of leadership styles is advanced in developed countries; however, in developing countries such as Ecuador studies on this topic are scarce. This study aims to describe the leadership styles of managers of SMEs in Ecuador and the relation between the different styles. The demographic characteristics of the leaders are taken into consideration in order to establish if they have an impact on the pattern used